UniTask: Task Management System for UNIMAS Students - Fion Jee, Wen Xuan; Mohamad Johan, Ahmad Khiri (UNIMAS Publisher, 2025)
UniTask is a task management web application created for students at the University of Malaysia, Sarawak (UNIMAS). Unlike general task management tools, it is designed for a university setting. It includes features like group project management, schedule integration, and personalized reminders. The system focuses on multitasking and efficiency. It tracks deadlines and prioritizes tasks automatically. This gives students a simple way to handle coursework, assignments, and project deadlines. The development process involved engaging with UNIMAS students, including surveys and focus groups, to ensure the system meets their specific needs. Through employing Agile methodology, UniTask prototype was improved step by step using feedback from users, ensuring adaptability and ease of use. The system’s customization options allow students to align UniTask with their personal study habits and preferences, enhancing individual productivity. As a result, UniTask empowers students to organize academic tasks more efficiently, supports collaboration on group projects, and ultimately aims to improve academic performance by allowing for automated deadline tracking and task prioritization, establishing itself as an essential tool for success at UNIMAS.